Particles deposition on microfiltration permeable boundary: Modeling and simulation with two-ways coupling sphere model in a turbulent flow. Issue 4 (15th June 2015) - Zhang, Wen-Juan; Ruan, Xue-Hua; He, Gao-Hong; Ma, Yong-Liang; Liu, Yuan-Fa
Abstract : Purpose: – The permeate flux in microfiltration (MF) declines sharply with time due to membrane fouling, which seriously restricts its use in industrial applications. The purpose of this paper is to investigate particles deposition in MF processes, and propose a three-dimensional numerical model that focuses on particle-fluid flow and considers both permeable boundary conditions and cake deposition. Design/methodology/approach: – The two-ways coupling model was solved using Euler-Lagrange methods in which the suspended particle was traced by a hard sphere model and the fluid was simulated using large eddy model. Findings: – The numerical results predicted based on this model demonstrated the permeate flux increased as trans-membrane pressure and inlet velocity increased but decreased with an increase in feed concentration. Research limitations/implications: – Good agreement was observed between the values obtained with the model and experimental values from the literature. The error is less than 20 per cent both permeate flux and cake thickness. In addition, a precise visualisation of cake morphology with filtration time was provided. Originality/value: – These analyses allowed for an estimation of the three-dimensional motion of suspended particles in turbulent flow. It saves manpower and financial resources for experiment, which possess important theoretical and industrial significance.